EXPERIMENTAL VERIFICATION OF THE EFFECTIVENESS OF JET ABRASIVE IMPACT ON THE RAILS TO IMPROVE THE FRICTION PROPERTIES OF «WHEEL-RAIL» TRIBOCONTACT (Transport systems and technologies, 2018)
The article describes the results of experimental verification of the effectiveness of jet abrasive impact on rails as one of the possible ways of increase of efficiency of use of sand to improve frictional contact properties of «wheel-rail» system. Jet-abrasive impact ensures a directed flow of abrasive material under the action of compressed air on the surface of the rail, affecting the friction condition of the wheel-rail contact, which consists in the removal of surface contamination, the formation of surface roughness, the actual supply of sand in the contact of the wheel with the rail. Under frictional properties means thedependence of coefficient of sliding friction rolling sliding temperature in contact. According to the dependencies characteristics of the clutch for the selected friction conditions were built. As the initial frictional state of the surface of the rail were used: clean and dry surface; moist surface; surface covered with diesel fuel; surface covered with used oil. Statistical processing of obtained experimental data shows that the sand slightly increases the coefficient of friction and creates more adverse conditions of contacting for interactive surfaces. In jet-abrasive impact is the destruction of contaminants on the surface of therail, as well as their carryover reflected shock, which carries refined products from the zone of contact. Thus on the surface of the rail is virtually no abrasive material that can cause a resistance to movement, as in the case of the use of sand in the studied feedingperformance.
Keywords: abrasives, friction coefficient, abrasive jet impact, frictional transmission efficiency